GIS التحليل المكاني والاحصائي لحوادث الحرائق في مدينة الناصرية لعام ٢٠١٥ باستخدام نظم المعلومات الجغرافية (University of Thi-Qar Journal for Engineering Sciences, 2017)
Geographic Information Systems (GIS) have contributed in the optimal planning of cities in general, and evaluate the distribution of services locations within cities, including the civil defense service in particular. The city of Nasiriyah was chosen to study the different geographic data collection belonging to the reality of the civil defense service offered, in addition to the collection of more than 600 fire accident have been processed for 2015, and using ArcGIS program has been the introduction and management of different data and evaluated statistically, and it turned out that the ratio the largest of fire accidents had occurred within the civil defense center Numan service scope and earned the Al-Sharquia district (south east of the city), the largest number of them. The main conclusions of this study is that 63% of fires in open areas were causes messes the kids, either the main recommendations of the study can be summarized the need to increase the number of detachments of civil defense during the summer, especially the need to use the Global Positioning System GPS to ensure the precise location of the incident and therefore increased processing speed.